Między samotnością a solidarnością. Wokół problematyki podmiotowości w późnej krytyce literackiej Stanisława Barańczaka - Trubicka, Hanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2011)
The issue of subjectivity is raised in the theoretical and critical works on poetry authored by Barańczak, so to speak, marginally. Despite the fact, the issue of identity seems to constitute their core subject and is organically related to other relevant key threads such as, primarily, the issue of the “ethics of distrust”. Interestingly enough, the ambivalence of the situation of an individual, — placed somewhere between the individualistic and the community perspective — which is emphasized by Stanisław Barańczak by making rhetoric figure of paradox particularly privileged — is also expressed in the language in which the critic describes the problem. His observations come down ultimately to one thing: a consistent search in different writers for a confirmation of the assumption on the paradoxical nature and bi-dimensionality of human existence.